The challenges Indonesian oil palm smallholders face when replanting becomes necessary, and how they can be supported: A review - Heinrich Petri; Dienda Hendrawan; Tobias Bähr; Rosyani Asnawi; Oliver Mußhoff; Meike Wollni; Heiko Faust (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2022)
Three decades after the establishment of many smallholder oil palm plantations, large areas of oil palm will require replanting soon or are already overmatured. The process of replanting offers a unique opportunity to redesign plantations, close yield gaps, boost productivity and therefore secure income and livelihoods, but requires knowledge, inputs and financing. If postponed or done incorrectly, replanting could further exacerbate existing challenges in smallholder oil palm cultivation, both socioeconomic and environmental. In this review, we collect relevant literature on replanting of oil palm, especially in the realm of smallholder cultivation, to highlight the challenges smallholders will face when replanting. We find that access to inputs, finances and know-how differ greatly between groups of smallholders. This will likely affect smallholder's decisions when, how and what to replant. Information on replanting, proper training, access to high-quality seedlings as well as eligibility for public replanting funds will determine the success of smallholder replanting efforts in Indonesia but are distributed unevenly currently. We finish the review with recommendations for both policy-makers and researchers on how to overcome the challenges replanting holds and capitalize on the opportunity replanting offers rather than exacerbating existing issues.
Keywords: 330; oil palm; replanting; smallholder; livelihood; Indonesia; Sumatera